Aplicación de una auditoría tributaria a la empresa de lácteos Ecualac ubicado en la provincia de Pichincha cantón Mejía, en el período del 01 de enero al 31 de diciembre del 2012 - Chicaiza Pilliza, Marcia Jimena (2015)
This research was conducted in the “Ecualac” enterprise because there are weaknesses in how to comply with tax obligations as late submission of withholding in some months, fines and interest, proxy statement Value Tax added, the tax information is filled in chronological order, in the tax reconciliation the accountant does not take into account non-deductible expenses generated by the fines and interest, for the aforementioned drawbacks arises the need to apply to the Tax Audit entity for the period from January 01st- to December 31 st 2012, in order to comply with the statements on the dates set and thus optimize the resources of the institution. A descriptive research, inductive, deductive and analytical methods, techniques applied such as interviews, surveys, and observation. Were used in this study. This process allowed to obtain relevant information about this topic. The implementation of the audit gave as a result a final report on compliance with the formal obligations to the taxpayer, this document contains conclusions and recommendations on the findings to be considered by the Manager and Accountant to improve tax administration.